Pure vanadium and titanium for low activation alloys - Pylypenko, M.M.; Lavrinenko, S.D. (Вопросы атомной науки и техники, 2016)
The refining processes of vanadium and titanium from metal and gas impurities by physical methods in vacuum are considered. The effectiveness of using electron-beam melting, zone recrystallization and electrotransport for purification of these metals is shown. Vanadium and titanium in a purity of more than 99.99% have been produced.